Correlates of Emergency Department Use among Individuals with Bipolar Disorder enrolled in a Collaborative Care Implementation Study - Waxmonsky, Jeanette (Psychiatr Serv, 2016)
OBJECTIVES: The study assessed correlates of emergency department use among individuals with bipolar disorder receiving a collaborative care program. METHODS: Community-based clinics from two states implemented the evidence-based Life Goals-Collaborative Care Model (LG-CC), which included self-management sessions and care management contacts. Logistic regression analysis was used to determine participant factors associated with 12-month emergency department use after LG-CC implementation. RESULTS: Among 219 participants with non-missing baseline and 12-month data, 24.2% (n=53) reported at least one emergency department visit. Participants with homelessness history (OR=3.76; 95% CI=1.39–10.2; p=.01) or 5 or more care management contacts (OR=2.62; 95% CI=.1.00–6.95; p=.05) had higher probability of emergency department visit, adjusting for demographic and clinical factors including physical health and hospitalization history. CONCLUSIONS: Individuals with bipolar disorder and history of homelessness were more likely to use the emergency department despite enrollment in a Collaborative Care program, suggesting a greater need for more intensive care coordination.